The Use of Animal Lexeme in Sikka-Krowe Proverb (Ethnolinguistic Study) - *Rikardus Nasa; Amatus Leo; Nur Syamsiah Ekhsan (Universitas Syiah Kuala, 2022)
This research aims to find out animal lexemes used in the Sikka-Krowe proverb and the lexical and metaphorical meanings of each animal lexeme used and identify the realm in the Sikka-Krowe proverb. This research used qualitative research methods and the data of this research consist of primary data where primary data obtained through interview and secondary data where the data collected by literature study process. The chosen informants in this research are chieftain and traditional stakeholder. Of course, both informants are native speaker of Sikka-Krowe language. The data collection techniques used are literature study and interview. Data analysis techniques consist of data reduction, data display (data presentation) and conclusion drawing/verification. The result of this research shows animal lexeme proverbs in Sikka-Krowe language. The animal lexeme proverbs found and classified according to six animal classifications, they are; mammals, eves/birds, reptiles, amphibians, fish and insect/invertebrate. The research proves that animal lexeme in the proverbs of Sikka-Krowe that shows the Sikka-Krowe communitys view of life which were divided into four domains of use, namely it was used in the realm of family life, community life, spiritual life, and the work environment.